Climate and Weather Informational Services and Products for Maize and Wheat Farmers in Uasin Gishu County, Kenya - Murgor, D. K.; Cheserek, G.; Nduru, G. M. (Africa Environmental Review Journal, 2018)
With the prevailing climatic variability presenting globally, nationally and at local levels in all countries, availability in real time and the subsequent uptake of climate and weather information by farmers in their crop production planning and production process becomes very critical. This is because attaining improved and sustained high crop yield in a rain fed agricultural system largely depends on accurate timing of rainfall onset and cessation dates during growing and harvesting season. To understand this phenomenon, a study was conducted among maize and wheat farmers in Uasin Gishu County with the objective to determine the types and sources of information on climate and weather available to them for use at the farm level. The study was conducted in Moiben, Kesses and Soy sub counties of Uasin Gishu County. The study adopted stratified and random sampling procedure to capture representative sample of farmers. A sample of 399 farmers participated in the study in addition to 12 key informants. A pre-tested semi-structured questionnaire and an interview schedule were the main data collection tools. Chi-square and independent sample t-test were employed in the analysis using SPSS (V.16). Results were considered significant at α=0.05. The findings showed that 49.2% reported not to receive any product or service for use in their farming activities. However, 19.8% received Farmer’s Guide product while 19.1% received targeted information for maize and wheat farmers showing them what variety to plant, where to plant and when to plant. There is low access to supportive climate and weather information by majority of farmers and with the prevailing climatic variability being witnessed locally by farmers at the farm level, farmers will continue incurring losses. The findings further reveal the fact that the experience gained by a farmer over time doing maize and wheat greatly influences their decision at the farm level. Similarly, their traditional understanding on rainfall indicators influenced their activities more and all these form a larger portion of source of climate and weather information to them as indicated by 84.9% and 36% respectively. Agricultural Extension Officers accounted for 46.2% while 50% indicated that their source of information is their fellow farmer. All these reveal a vulnerable farming population in times of climatic variability being witnessed all over the world. The need to repackage climate and weather information to formats accessible and easily understood messages by farmers will be catalytic in aiding access to the information and will help create ownership and sustainability. Agro-meteorological services should target the use of mobile phones especially messaging service to disseminate their products and services to the farmers as they are widely accessible to them.